The Wounded Voice: Forms of Oppression Against Women in the Film Tuhan, Izinkan Aku Berdosa - Fitriani, Rahmania Alya; Sa’adah, Dwi Nur; Nuzula, Firdausin; Shofah , Novia Adibatus (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This article analyzes the forms of physical and emotional oppression experienced by Kiran in the film Tuhan, Izinkan Aku Berdosa directed by Hanung Bramantyo, as reflected through the character’s dialogues. The film serves as a mirror of a social reality that continues to marginalize women, while simultaneously offering a narrative of resistance in silence. This study employs a qualitative descriptive method using paralinguistic theory and feminist literary criticism. In the paralinguistic analysis, the focus is placed on examining Kiran’s vocal expressions such as pitch, vocal quality, and tone during her dialogues. In the feminist literary critique, the study focuses on Kiran’s dialogues that reveal inner turmoil, involvement in promiscuity, and moral pressure within a patriarchal religious environment. Through this analysis, the study illustrates how gender-based injustice is represented in the film. The findings indicate that Kiran’s manner of speech reflects symptoms of post-traumatic stress disorder (PTSD), including re-experiencing, avoidance, negative thoughts, despair, and the inability to voice her rights. Furthermore, the film highlights how women’s bodies and spiritualities are regulated by social and religious systems.